ACCOUNTING INFORMATION AND LENDING DECISION: DOES SUSTAINABILITY DISCLOSURE MATTER? - Aifuwa, Hope Osayantin; Saidu, Musa; Enehizena, Osaruese Cynthia; Osazevbaru, Albert (Copernican Journal of Finance & Accounting, 2020)
Lending decisions of banks is a function of accounting information of borrowing firms, however, in contemporary times the quality of their accounting information is not encouraging to be used as a yardstick in taking lending decision. Against this backdrop, we investigated the impact of accounting information on commercial banks’ decision to Manufacturing firms in Nigeria. A sample of thirteen industrial listed firms was used. Descriptive and inferential statistics were employed to summarize the data and to draw inference on the population studied. We employed the Ordinary Least Squares in testing the hypotheses stated. Findings revealed that monetary value of collateral positively affects lending decisions of banks, profit level of borrowing form negatively influence the lending decision of banks, while corporate sustainability disclosure positively but insignificantly impact on banks’ lending decisions. The study concluded that accounting information affect banks’ lending decisions, also although corporate sustainability insignificantly influence bank lending decision, it does not matter.